Maternal and fetal outcomes with increasing maternal age during pregnancy: a hospital-based study - Mavelil, Anjana; Nandan, Neetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: In recent decades, delayed childbearing has become increasingly common due to socio-economic and professional factors, leading to a rise in pregnancies among women aged 30 years and above which may have an impact on obstetric and perinatal outcomes. Aim was to evaluate the association between increasing maternal age and adverse maternal and neonatal outcomes in singleton pregnancies beyond 30 years of age. Methods: Total of 207 pregnant women aged >30 years were recruited and categorised into three age groups: 30-34 years, 35-40 years (AMA- advanced maternal age) and >40 years (VAMA- very advanced maternal age). Maternal and neonatal parameters were noted. Results: The incidence of fibroid complicating pregnancy, thyroid disorders in pregnancy significantly increased with increase in maternal age. The risk of gestational diabetes, gestational hypertension was more with increase in age (AMA, VAMA group) but preeclampsia was noted more in age group of 30-34 years. Preterm delivery and induction of labour was more in 30-34 years of age. The rate of caesarean section showed a steady increase after 35 years of age. Postpartum hemorrhage was two times more and gestational hypertension was 5 to 7 times higher in AMA and VAMA groups compared to 30-34 years age group. Conclusions: There was increase in fibroid complicating pregnancy and thyroid disorders in pregnancy in women >35 years of age. The association of GDM, gestational hypertension, the need for caesarean section was also high with increase in maternal age >35 years of age. In 30-34 years of age group preeclampsia, preterm delivery and induction of labour was found to be higher.